ELECTROMAGNETIC AND SOUND INSULATION PROPERTIES OF COMBINED SHIELDS BASED ON THE NEEDLE-PUNCHING MATERIAL AND FRAGMENTS OF ALUMINUM FOIL - H.D. A. Abdulhadi; Е.А. A. Almashat; O. V. Boiprav; V. A. Bogush; A. M. Prudnik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
A method for creating the electromagnetic radiation shields, which consists in fixing fragments of aluminum foil on the surface of a needle-punched carbon-containing material has been proposed. In accordance to the proposed method the shield samples have been made. The fragments of the used aluminium foil were in the form of rectangles or half rings the overall dimensions of which didn't exceed 20 mm. Using an automated meter of transmission and reflection coefficients SNA 0.01–18, shielding characteristics in the frequency range 0.7–17 GHz of the shield samples made in accordance with the proposed method have been obtained. Using the measuring stand, the main components of which were a white noise generator, power amplifier, speaker, sound analyzer MANOM-2, in the frequency range 20–16000 Hz, the soundproofing properties of the shield samples made in accordance with the proposed method have been obtained. It was shown that the values of the electromagnetic radiation reflection coefficients in the frequency range of 0.7–17 GHz of the investigated shields vary from –0.5 to –19.0 dB, and the electromagnetic radiation transmission coefficient in the specified frequency range vary from –2.0 up to –18.0 dB. It was found that the of electromagnetic radiation reflection coefficient values in the frequency range 0.7–17 GHz and the electromagnet radiation transmission coefficient values in the frequency range 6–17 GHz of the shields made in accordance with the proposed method using fragments of aluminum foil in the form of half rings, by 1,0–6.0 dB below the same values of the shields made using fragments of aluminum foil in the form of rectangles. It was determined that the studied shields provide sound attenuation by 2–3 dB in the frequency range from 20–16000 Hz. In view of the obtained results, shields manufactured in accordance with the proposed method are recommended for use in order to protect information circulating in the premises from leakage through the acoustic channel and the channel of secondary electromagnetic radiation.